An annotated catalog of the type material of Adephaga and Myxophaga (Coleoptera) deposited in the Florida State Collection of Arthropods in Gainesville, Florida, United States of America - Keller, Oliver; Schnepp, Kyle E.; Ashman, Krystal L.; Turnbow, Robert H.; Skelley, Paul E. (Zootaxa, 2020)
The Florida State Collection of Arthropods (FSCA) ranks in the top 10 largest Coleoptera collections in the United States of America with in excess of 1.5 million pinned beetles and significant amounts of materials in bulk collections and other unprocessed samples. The suborder Adephaga currently comprises approximately 34,000 species in 10 extant families and the suborder Myxophaga contains approximately 94 species in four extant families. The FSCA owns type material in the adephagan families Carabidae, Dytiscidae, Gyrinidae, Haliplidae, and Noteridae. The myxophagan holdings in the FSCA include type material from the families Hydroscaphidae and Lepiceridae. There were no holdings of type material in the suborder Archostemata at FSCA. This catalogue documents the FSCA type material for 253 species in 80 genera across the two suborders. A total of 3,528 type specimens are reported, including 60 holotypes, 36 allotypes, 3,426 paratypes, and six syntypes.